Heatwave-Like Events During Development Are Sufficient to Impair Bumblebee Worker Responses to Sensory Stimuli - Perl, Craig D.; Johansen, Zanna B.; Moradinour, Zahra; Guiraud, Marie; Restrepo, C. E.; Wen Jie, Vun; Miettinen, A.; Baird, Emily (Frontiers in Ecology and Evolution, 2022)
Heatwaves are increasingly common globally and are known to have detrimental impacts on animal morphology and behaviour. These impacts can be severe, especially if heatwaves occur during development, even on animals that can regulate the temperature of their developing young. The onset and duration of heatwaves are stochastic and therefore may affect all or only part of development. In the heterothermic bumblebee Bombus terrestris, elevated temperatures over the entirety of development cause morphological changes in adults, despite their capability to regulate brood temperature. However, the effects of heatwaves that occur during a short period of development are unclear. We test the impact of elevated developmental temperature during the latter fraction of development on the behaviour and morphology of adult worker B. terrestris. We show that exposure to elevated temperature over a portion of late development is sufficient to impair the initial behavioural responses of workers to various sensory stimuli. Despite this, exposure to elevated temperatures during a period of development did not have any significant impact on body or organ size. The negative effect of elevated developmental temperatures was independent of the exposure time, which lasted from 11-20 days at the end of the workers’ developmental period. Thus, heat stress in bumblebees can manifest without morphological indicators and impair critical behavioural responses to relevant sensory stimuli, even if only present for a short period of time at the end of development. This has important implications for our understanding of deleterious climactic events and how we measure indicators of stress in pollinators.